Rowan Williams on Christian Doctrine - Wainwright, Geoffrey (Scottish journal of theology, 2003)
The skilfully arranged pieces collected in Rowan Williams's On Christian Theology are regarded by Geoffrey Wainwright as an informal dogmatics, an instance of ‘open system’. A subtle thinker and writer, Williams starts from the heartlands of the Christian faith and explores its boundaries. His work is evaluated in this article according to what he himself establishes as the celebratory, communicative, and critical styles of theology. Williams's kenotic trinitarianism is matched with his Abelardian view of the atonement, which seems to neglect some scriptural and traditional elements that a more Anselmian understanding would take into account. Freedom is a key notion for Williams but needs more definition in relation to ‘choice’; and his location of the church remains institutionally imprecise. Wainwright particularly appreciates Williams's exposition of the doctrine of creatio ex nihilo and the aesthetic, doxological, and eschatological dimensions of his ethical thought. The book under discussion is disarmingly modest in tone, and the author himself declares that repentance is always in order for a theologian.